The Effect of High-Dose Statin Therapy on Reducing Major Adverse Cardiac Events in Diabetic Patients: A Systematic Review and Meta-Analysis - Chaudhari, Karan Rajeshkumar; Hack, Sarah; Khan, Sumaiya; Meka, Lakshmi Malavika Reddy; Munir, Ahsan; Zumman, Dost Mohammad; Ishola-Gbenla, Khadijat; Mohammed, Zaki Ur Rahman; Abid, Marium; Essani, Binish; Bhindar, Shah Zaib; Mirza, Muhammad Sohail S. (Cardiology and Cardiovascular Medicine, 2025)
High-dose statin therapy has been widely used for cardiovascular risk management, particularly in diabetic patients who are at high risk of major adverse cardiovascular events (MACE). This systematic review and meta-analysis aimed to assess the effectiveness of high-dose statins in reducing MACE in diabetic patients while also evaluating the potential risk of new-onset diabetes mellitus (NODM). A comprehensive search was conducted across databases, including PubMed, Cochrane Library, and Google Scholar, focusing on studies published between 2020 and 2025. The inclusion criteria targeted studies that compared high-dose statin therapy with either lower doses or placebo in diabetic populations, with MACE and NODM as primary outcomes. The pooled analysis revealed a moderate positive effect of high-dose statins on reducing cardiovascular events (effect size = 0.90, 95% CI: 0.68–1.12), though there was significant variability across studies. Additionally, high-dose statins were associated with an increased risk of NODM, consistent with other research in the field. The I² statistic was 91.18%, indicating substantial heterogeneity across studies. Publication bias was minimal, as assessed by funnel plots and Egger’s regression. Quality assessment using the RoB 2 and NOS tool revealed variability in methodological rigor, with some studies showing higher risks in randomization and blinding. Despite the benefits of statin therapy in preventing cardiovascular events, the potential for increased diabetes risk suggests the need for a balanced, personalized approach. Further research is required to optimize statin regimens, minimize side effects, and refine treatment strategies for diabetic patients at cardiovascular risk.